ChemInform Abstract: Synthesis of (‐)‐ and (+)‐Gummiferol via Asymmetric Synthesis of Glycidic Amides. Issue 43 (7th October 2016) - Garcia‐Ruiz, Cristina; Cheng‐Sanchez, Ivan; Sarabia, Francisco
Abstract: An efficient syntheses of the natural and non‐natural gummiferols are achieved according to a novel asymmetric methodology of diepoxy alkyne formation based on a new class of chiral sulfonium salts.